Prognostic value of preoperative plasma fibrinogen level and platelet-to-lymphocyte ratio (F-PLR) in patients with localized upper tract urothelial carcinoma - Huang, Jiwei (Oncotarget, 2016)
PURPOSE: Hemostatic factors is thought to have a potentially significant role in progression and metastasis of malignant tumors. We investigated the prognostic value of preoperative plasma fibrinogen level and platelet-to-lymphocyte ratio (PLR) in localized upper tract urothelial carcinoma (UTUC). MATERIALS AND METHODS: A total of 481 patients who underwent radical nephroureterectomy for localized UTUC (pTa-4N0M0) were identified between January 2002 and June 2013. Patients were assigned a F-PLR score of 0, 1, or 2 based upon the presence of elevated plasma fibrinogen level, an elevated PLR, or both. The association between F-PLR score and clinicopathological variables was analysed. RESULTS: The optimal cut-off value of plasma fibrinogen and PLR for overall survival stratification was determined to be 4.22 and 241.2. Kaplan–Meier analysis revealed significant differences in cancer specific survival (CSS) and overall survival (OS) among patients with F–PLR scores of 0, 1 and 2. Multivariate analysis identified higher F–PLR score as an independent risk factor for CSS (P < 0.001) and OS (P < 0.001). The estimated c-index of the multivariate model for CSS and OS increased from 0.772 and 0.756 to 0.799 and 0.784 when F–PLR score added, which was higher than fibrinogen level, PLR or neutrophil-to-lymphocyte ratio added. CONCLUSIONS: Preoperative F-PLR score is a negative independent prognostic factor for survival outcomes in patients with localized upper tract urothelial carcinoma. Preoperative F-PLR score may become a useful biomarker, particularly because of its low associated cost and easy accessibility.